Measuring psychopathology - Farmer, Anne (Oxford University Press, 2002)
Measuring Psychopathology describes the methods by which the signs and symptoms of mental disorder are elicited, examined and evaluated.; Written for the non-clinical researcher as well as for those with clinical experience, the authors start by considering the question 'what is psychopathology?' They then employ a historical perspective to explain why and how mental disorders are currently classified, and how the use of an operational approach to diagnosis was adopted. The use of operational criteria to define psychiatric disorder has facilitated the development of standardised interviewing techniques, questionnaires and rating scales. These tools are all covered in some detail, not only with regard to adults with mental disorders, but also with reference to special and challenging groups such as children and the elderly, and those with a learning disability, substance misuse, or who have a personality disorder.; The strengths and weaknesses of current methodologies are explored and debated as well as the future diagnostic needs for research in the 21st century.; Essential reading for clinicians and non-clinical scientists engaged in research on psychiatric disorders, trainees and junior psychiatrists, and clinical psychologists.